An electromyographic and impact force study of the overhand water polo throw - Clarys, J. P.; Cabri, J.; Teirlinck, P. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
Ten elite water polo players were monitored during the performance of the overhand throw from 4 m and 8 m distance to a force platform target using surface EMG of arm, trunk and lower limb muscles. The impact force of the ball was simultaneously registered with the raw EMG. The linear envelope was used for pattern and throwing synchronisation detection, the iEMG was used as a reference value for muscular intensity and the force plate target gave an approximation of throwing precision. Good throwing synchronisation was initiated by the eo-contraction of the M. biceps femoris and the M. rectus femoris followed by an important activity of the M. pectoralis major. The actual swing phase showed an important eo-contraction of the M. triceps brachii with the M. biceps brachii. The impact forces ranged from 598 N to 981 N (4 m) and 402 N to 961 N (8 m). The impact force profile of the subjects was not reflected in the precision scores.